RF wall conditioning at the Uragan-2M with use of high vacuum cryogenic trap - Korovin, V.B.; Baron, D.I.; Kozulya, M.М.; Chernichenko, V.Ya.; Kramskoy, E.D.; Pashnev, V.K.; Mozetič, M. (Вопросы атомной науки и техники, 2015)
The results of evaluating the effectiveness of the vacuum chamber wall conditioning procedure by the use VHF of continuous discharge and RF pulse discharge that were applied either separately or in combination with each other in helium atmosphere at Uragan-2M are presented. The high-vacuum cryogenic traps are enabled in these experiments. Some amount of gas pumped from the vacuum chamber is condensed on the surfaces of cryogenic traps integrated in the input branch pipes of the vacuum system. Periodically, one trap is separated from the chamber and from the pump by vacuum valves and warmed up what led to release of the condensed gases into the enclosed volume. The value of pressure Pg inside this volume is proportional to the amount of pumped gas and, consequently, to the effectiveness of the wall conditioning process. It was found that the value Pg in the combined VHF + RF discharge is 2-3 times higher than in the case of using only pulsed RF discharge. Приведены результаты ВЧ-чистки в стеллараторе Ураган-2М с использованием УКВ непрерывного разряда в атмосфере гелия. При этом часть откачиваемого газа конденсировалась на криогенную ловушку. Процесс чистки контролировался измерением давления газа Pг в отсеченном объеме с ловушкой после ее отепления. Значение Pг пропорционально количеству откачиваемого газа. Обнаружено, что количество сконденсированного на ловушке газа при комбинированном УКВ+ВЧ-разряде в 2-3 раза выше, чем в случае использования только импульсного ВЧ-разряда. Наведено результати ВЧ-чистки в стелараторі Ураган-2М з використанням УКХ безперервного розряду в атмосфері гелію. При цьому частина відкачуваного газу конденсувалась на криогенну пастку. Процес чищення контролювався за допомогою вимірювання тиску газу Pг у відсіченому об`ємі з пасткою після її отеплення. Значення Pг пропорційно кількості відкачуваного газу. Виявлено, що кількість сконденсованого на пастці газу при комбінованому УКХ + ВЧ-розряді в 2-3 рази вище, ніж у випадку використання тільки імпульсного ВЧ-розряду.